Business driven automation testing framework - Anand, R.; Arulprakash, M. (International Journal of Engineering and Technology, 2018)
Due to versatile growth of software industry, we need to invent and adapt new technologies to reduce the production cost and to increase the quality. Now a days the industry is moving towards the 100% of automation testing and is being done by the different kind of users. The same test script will be executed by the domain expert instead of a technical expert, so we can’t expect him to understand the complexity of scripts and to relate the test script with business scenarios. To simply the users view of automation testing we need a layer to hide the technical implementation and to introduce some simplified way to understand the test script and relate with business scenarios, if needed he should be able to modify the test scripts without having the technical knowledge. The gap between the customers’ expectations and the actual product behavior will be reduced using this proposed approach.